Preliminary analysis: Engaging learning via new Web 2.0 medium - Facebook (Abstract) - Rosnida Abu Bakar,; Raziana Che Aziz,; Norfardilawati Musa ,; Nor Aisyah Fadil, (2012)
This paper presents the use of online social network (OSN) applications, Facebook, as a tool for e-learning. The traditional e-learning medium in Open University Malaysia (OUM) is using the learning management system or learning portal called the “My Virtual Learning Environment” (myVLE), which is based on web 2.0 applications. If compared to Facebook, the myVLE is not really known to the public. Hence, we believe that the various features possessed by Facebook, such as facilitating online discussion, sharing links and resources, facilitating the conduct of Q&A sessions, uploading field trip/project photos and videos and much more, can be maximized as a tool that can empower educators and students to engage, interact, share and learn in an e-learning environment. Furthermore, Facebook is applicable to many types of devices ranging from personal desktop computer to mobile devices such as Smartphone and tablets. It is compatible with numerous operating systems and its features such as private group and event scheduling, are easy to learn and use. In this study, we used Facebook to investigate how our students feel about using this online social network for e-learning apart from the existing learning management system, myVLE. Most of the higher education institutions are discovering that new models of teaching and learning are required to meet the needs of a generation of learners who seeks greater autonomy and connectivity as well as the opportunity to experience social learning. Traditional approaches to teaching and learning are typically based on prepackaged learning materials, fixed deadlines, and assessment task and criteria defined by educators. However, today’s students demand greater control of their own learning and technology is a way to meet their needs and preferences. Thus, the aim of this paper is to explore how Facebook is suitable as an e-learning tool for students. It is not about replacing our existing e-learning platform (myVLE), but about collaborating and empowering students with more tools in e-learning to make them feel engaged and motivated, especially in distance education. Oncology Nursing students were used as the sample for this study. (Abstract by authors)